Additive Manufacturing of Neodymium-Iron-Boron Permanent Magnets - Urban, Nikolaus; Kühl, Alexander; Glauche, Markus; Franke, Jörg (2018 8th International Electric Drives Production Conference (EDPC), 2018)
Keywords: Magnetic hysteresis; Magnetic properties; Powders; Perpendicular magnetic anisotropy; Additives; Metals; Additive Manufacturing; Rare Earth Magnet; NdFeB; Printed Magnet; Net Shape Magnet

A Microservice-Based Architecture for Flexible Data Acquisition at the Edge in the Context of Hairpin Stator Production - Raffin, Tim; Mayr, Andreas; Fuchs, Jonathan; Baader, Marcel; Morello, Andreas; Kühl, Alexander; Franke, Jörg (2021 11th International Electric Drives Production Conference (EDPC), 2021)
Data-driven technologies such as machine learning promise great potentials for electric drives production. However, present information systems do not allow flexible and reliable accumulation of high-dimensional data such as images and time series, so feature-rich data are often discarded in practice. The advent of edge computing and microservice-based software architectures in recent years enables low latencies, high data integrity, and flexibility towards different communication protocols, thus offering new possibilities to accumulate data in a manufacturing environment. Hence, this paper proposes a microservice architecture deployed on the edge that serves as a communication layer between data sources and downstream data analytics capabilities. The architecture's flexibility is demonstrated and validated on different process steps along the process chain of hairpin stator production. In conclusion, the developed microservice architecture is suitable for reliable data acquisition at the edge and can enable subsequent machine learning analyses across the process chain.
Keywords: Software architecture; Soft sensors; Data acquisition; Time series analysis; Microservice architectures; Production; Computer architecture; Edge computing; data analytics; Machine learning; Hairpin technology; electric drives production

Analysis of induction-based thermal demagnetization of a permanent magnet rotor in the context of recycling - Ihne, Thorsten; Wieprecht, Nico; Hahn, Roman; Franke, Jörg; Kühl, Alexander (2023 13th International Electric Drives Production Conference, 2023)
Rare Earth (RE) Magnets are a key for many green technologies causing continuously increasing demand in the European Union (EU). Alongside motors for e-mobility and generators in wind turbines, compressors in domestic heat pumps represent a potential lever for slowing climate change. On the other hand, the dominant market power of the PR China results in a high supply chain risk. Therefore, the EU has declared these elements as critical raw materials of the highest category and plans a compulsory recycling share of 15% until 2030. Currently, no systematic recycling activities for RE magnets are operated on an industrial scale. In the present paper a concept for the extraction of RE magnets from rotors of HVAC compressors is presented. The focus is set on the thermal in-situ demagnetization by induction which is crucial for the disassembly of the magnets. This process ensures efficient heating to temperatures above the individual Curie temperatures so that interfering reaction forces are eliminated. Systematic test series are carried out based on an experimental set-up to identify the main process parameters and restrictions. The achieved results are analyzed and are evaluated regarding the transferability to a potential series process.<br

Analysis of Production Influences on the Transmission Efficiency of Wireless Power Transfer Systems - Kneidl, Maximilian; Fuß, Tobias; Weigelt, Michael; Masuch, Michael; Kühl, Alexander; Franke, Jörg (2023 IEEE Wireless Power Technology Conference and Expo, WPTCE 2023 - Proceedings, 2023)
Wireless power transfer (WPT) systems for electric vehicles are a more customer-friendly and convenient way of charging. Moreover, it seems to be a promising solution to increase the range of electric vehicles without having to use larger batteries. In addition to the positioning of the transmitter and receiver coils, the fabrication of the individual coils can also have a crucial impact on the overall efficiency of the transmission. The main objective of this paper is to use simulation results and practical validation to determine which manufacturing processes in the automated production of inductive power transmission systems affect both system efficiency and transmission performance for inductive charging applications. From the analysis of the process steps, the resulting manufacturing deviations are determined and evaluated. First, the manufacturing influences under real conditions are determined by performance measurements. The results obtained can be used to perform a simulative loss analysis of the components. It thus provides knowledge that can be used to design and monitor each process step. Keywords - Wireless Power Transfer, Manufacturing, Simulation, Efficiency)
CRIS-Team Scopus Importer:2023-09-22

Approaches For The Physical Sorting Of Soft And Hard Magnetic Material Mixtures In The Context Of Rare Earth Recycling - Ihne, Thorsten; Hahn, Roman; Kühl, Alexander; Franke, Jörg (Proceedings of the CPSL 2024., 2024)
Rare earth (RE) elements applied for magnets are considered as critical raw materials by most industrial countries. On the one hand especially neodymium-iron-boron (NdFeB) magnets are essential for the current economic transformation as they are used for core technologies such as electric mobility and wind power causing continuously increasing demand. On the other hand, there is a significant supply chain risk due to poor market diversification and bad substitutability. This leads to various economic problems such as steady rising prices, price volatility and potential shortages. In addition, the primary production has a poor ecological footprint. In this context, the recycling of NdFeB magnets has a high economic, geopolitical and ecological potential. However, hardly any recycling is currently carried out on industrial scale due to technical and organizational difficulties. As magnetic extraction from end-of-life (EOL) products by dismantling is only economically feasible in specific cases, the implementation of a universally applicable process based on shredding and multi-stage sorting is essential. Intensive research is currently being carried out for the further processing of the pure NdFeB granulate, but there is a lack of reliable separation processes for the hard and soft magnetic components of the ferrous shredding fraction, which are similar in terms of many physical properties. Therefore, the present paper discusses approaches based on physical sorting principles to close the existing gap in the overall process chain. The solution preferred by the authors is based on a multi-stage process chain realized as a flow process, which primarily exploits differences with regard to the mechanical and magnetic characteristics.<br
Keywords: Rare Earth Magnets; Critical Raw Materials; Recycling; Physical Sorting; Hard And Soft Magnetic Materials

Approach for Advanced Mechanical Recycling Strategies of Rare Earth Magnets Applied in Traction Drives - Ihne, Thorsten; Hahn, Roman; Wieprecht, Nico; Franke, Jörg; Kühl, Alexander (Production at the Leading Edge of Technology, 2023)
Rare Earth (RE) Magnets are crucial for the green transition of the European Union (EU). This applies especially for e-mobility where RE magnets are used for highly efficient traction drives. Permanent magnetic motors offer the best efficiency, but the use of Rare Earth Elements (REEs) is related to several drawbacks. The magnets and the required raw materials are almost exclusively imported. This causes problems for European industry due to supply chain risks and continuously increasing prices. In addition, primary production is associated with a poor ecological footprint. Therefore, the EU has declared REs as critical raw materials with highest supply chain risk and plans a compulsory recycling share of 15% until 2030. Currently, no industrially applicable processes exist for systematic recovery of RE magnets. In this context the following paper should present approaches for an automated process chain starting with an end-of-life traction drive until the extracted and demagnetized magnets.<br
Keywords: Rare earth magnets; Recycling; Traction drives; Critical raw materials

Approach For Optimized Dismantling Strategies And Design For Recycling Of Electric Traction Drives - Hahn, Roman; Wieprecht, Nico; Ihne, Thorsten; Kühl, Alexander; Franke, Jörg (6th Conference on Production Systems and Logistics, 2024)
With the widespread adoption of electric vehicles (EVs), there arises a pressing need for sustainable processing of electric traction drives (ETDs) at the end of their life cycles. Current methods for dismantling and recycling ETDs often show inefficiencies in material recovery causing economic disadvantages and increased environmental impact. Of particular relevance is the recycling of rare earth (RE) magnets, which are extensively used in ETDs because of their superior magnetic properties. Given the scarcity of rare earth elements (REEs) and the environmental impact associated with their extraction, the need for efficient RE magnet recycling is of key importance. However, there is currently a lack of efficient dismantling processes and recyclability is often inadequate. By developing an optimized approach that focuses on adapted dismantling strategies and design for recycling, a critical gap in the sustainable production and disposal of electric vehicles will be closed. A crucial aspect is the design for recycling, enabling efficient recovery and reuse of materials and components. The approach presented in this paper combines different aspects such as material composition, modularity of components, standardization and good separability to optimize the design for recycling of ETDs. By providing optimized dismantling strategies as well as guidelines for the design for recycling, the transition to more environmentally sustainable transport systems is supported in addition to increased economic efficiency. <br
Keywords: Recycling; Reuse; Optimized Dismantling; Design for Recycling; Electric Traction Drives; Rare Earth Magnets; Permanent Magnet Synchronous Machine

A reference architecture for the operationalization of machine learning models in manufacturing - Raffin, Tim; Reichenstein, Tobias; Werner, Jonas; Kühl, Alexander; Franke, Jörg (Procedia CIRP, 2022)
Inherent characteristics of machine learning algorithms such as their probabilistic nature, their reliance on large datasets as well as their need for constant retraining pose major challenges to the operationalization of machine learning models (MLOps) in the manufacturing domain. As such systems are known to quickly accumulate technical debt due to system-level interdependencies of code, data, and models, clear abstractions boundaries are mandatory. Therefore, this publication derives a systematic functional decomposition of an MLOps system tailored to the manufacturing industry into specific domains and contexts. Moreover, a concrete deployment view is provided, and possible future research directions are discussed.<br

Automated and Flexible Production of Inductive Charging Systems as an Enabler for the Breakthrough of Electric Mobility - Weigelt, Michael; Masuch, Michael; Mayr, Andreas; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (Advances in Production Research, 2018)

Calculation of the Copper Filling Factor of Electric Traction Drives including Graphical Representation - Riedel, Andreas; Roessert, Alexander; Kühl, Alexander; Franke, Jörg (2019 22nd International Conference on Electrical Machines and Systems, ICEMS 2019, 2019)
In order to achieve a higher power density of electric traction drives, one significant optimisation variable is the copper filling factor. A self-developed MATLAB program makes it possible to graphically display the filling factors known from the literature in order to visualize optimisation potentials. It is possible to display quadratic, rectangular as well as trapezoidal slot geometrics with round wires or flat conductors. The different wire diameters and their isolation can be chosen from IEC 60317-0-1 or can be inserted manually. After entering the required parameters, the slot geometry is fitted with round or flat conductors according to the principle of the orthocyclic winding scheme. By varying the slot geometry and the wire parameters, the optimum filling factor for different applications can be determined graphically and mathematically, taking into account the assembly air.
CRIS-Team Scopus Importer:2020-02-21
Keywords: electric traction drives; filling factors; MATLAB; optimisation; tool

Challenges and Solutions for Contacting Insulated Litz Wire Structures in the Context of Electromechanical Engineering - Seefried, Johannes; Riedel, Andreas; Kühl, Alexander; Franke, Jörg (Springer Nature, 2022)
The contacting process for insulated copper wires is one of the most challenging operations in the field of electromechanical engineering. New technologies used by electric motors and inductive charging devices increases the complexity of this process. A major factor contributing to increased process complexity is the use of litz wires which consist of numerous individually insulated thin wires. During the contacting process, each of the litz wires must be reliably stripped as well as electrically and mechanically connected to each other or additional contact elements. Therefore, the purpose of this publication is to show and evaluate various contacting processes that exhibit high potential for use with different types of litz wires. In each process evaluation, both shaped wires for electric motor applications and high-frequency litz wires for inductive charging applications are considered. The results are compiled in a process matrix which shows the contacting processes suitable for each wire type as well as their corresponding advantages and disadvantages.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Contacting technologies; Litz wire; Wireless power transfer

Challenges in bonding processes in the production of electric motors - von Lindenfels, Johannes; Ziegler, Marco; Kneidl, Maximilian; Kühl, Alexander; Franke, Jörg (Proceedings of the 9th Congress of the German Academic Association for Production Technology (WGP), 2019)
In an effort to meet climate protection targets, countries around the world are promoting electro mobility. As a result of market growth, the worldwide production capacities for electric motors for traction drives is going to expand significantly. Besides, the existing technology must be adapted to automotive-specific life cycle requirements. On the product side, the electric machine has to reach maximum power densities in order to keep the required limitations of space and weight. Furthermore, a fully automated production process is essential to achieve high output rates and required quality standards. The application of new adhesives and bonding processes implements product-relevant properties in the production of components for electric motors. Moreover, the selection of adhesive systems and process parameters is crucial for cost-efficient and high quality manufacturing processes in mass production. In the production of permanent magnet synchronous machines, adhesives are used for joining of lamination stacks, fixation of magnets and the overall assembling of stator housings.The paper analyses and evaluates different adhesive systems in terms of their product and process capability using two cases of application. The results serve as a starting point for further automated process development and reveal the challenges of the adhesive application in production technology for electric motors.
Keywords: Quality; Security; Mobility

Challenges in Cost-effective Automated Detection of Enameled Flat Wires in the Context of Robot-based Stator Manipulation - Vogel, Alexander; Morello, Andreas; Mahr, Alexander; Franke, Jörg; Kühl, Alexander (2022 12th International Electric Drives Production Conference (EDPC), 2022)
Especially in the production of electric drives, highly efficient drives in new use cases are needed to reach global climate targets. To obtain maximum motor power with minimal motor weight, it is necessary to fill the stator slots with a maximum of copper. In the past, the round wire has been the state of the art. However, with increasing efficiency expectations, round wires cannot reach the performance targets anymore. Form coils, also known as hairpins, are one common technology with higher fill factors. In addition, winding processes with endless flat or rectangle wires are currently in development and could fulfill the demand for electric drives in the future. Accompanied by new joining solutions, this technology could lower the production cost on the one hand and reduce the contacting spots with potentially increased contacting resistance on the other hand. One challenge in the automation of their winding and joining is a fully automated process chain, starting with the winding process and ending with end-of-line testing. One thing, all process steps have in common is the requirement to detect the position of the wires with high precision. This detection is fundamental to subsequent steps, performed by smart robot-based machines.<br
Keywords: wire detection; flat wire; image recognition; stator manipulation; stator manufacturing automation; electric drives production

Challenges of Contacting Processes for Thin Copper Flat Wires in the Context of Electromechanical Engineering - Seefried, Johannes; Mahr, Alexander; Weigelt, Michael; Kühl, Alexander; Franke, Jörg (2021 11TH INTERNATIONAL ELECTRIC DRIVES PRODUCTION CONFERENCE (EDPC), 2021)
CRIS-Team WoS Importer:2022-04-29

Challenges of the Hairpin Technology for Production Techniques - Riedel, Andreas; Masuch, Michael; Weigelt, Michael; Gläßel, Tobias; Kühl, Alexander; Reinstein, Sebastian; Franke, Jörg (2018 21st International Conference on Electrical Machines and Systems (ICEMS), 2018)
The electrification of the drive train of passenger cars is currently undergoing an evolution from windings previously drawn in, which are known from industrially used electrical machines, to windings specially tailored to the requirements of mobile electric traction. A main trend is the use of pluggable shape windings, so-called hairpins. In order to fully exploit the economic advantages of this winding, elaborated production concepts and strategies are required. Due to the novelty and the currently ongoing innovation of these type of windings, the differentiated manufacturing possibilities per process step have not yet been fully defined. In view of the economic efficiency, high process speeds with increasing process reliability play a major role. The aim of this paper is to show a process chain of hairpin technology that is as universally valid as possible, to name the different alternatives for each process step and to explain their characteristic
Keywords: Wires; Windings; Insulation; Manufacturing automation; Production systems; Conductors; Hairpin; Process Chain; Production Technologies

Comparison of Additive Balancing Processes for Rotors in the Context of High Speed Electric Traction Motors - Masuch, Michael; von Lindenfels, Johannes; Seefried, Johannes; Mayr, Andreas; Schneider, Michael; Weigelt, Michael; Kühl, Alexander; Franke, Jörg; Hemmer, Christian (2019 9th International Electric Drives Production Conference (EDPC), 2019)
In the ongoing development of electric traction motors with increasing volumetric power density, concepts are being developed for rotational speeds of more than 30,000 rpm. These motors require an especially high balancing quality. Due to the unavoidable material and production fluctuations, a tuning of the mass distribution regarding the rotation axis is necessary. This balancing can be achieved by subtractive or additive process alternatives. In this paper, an overview of current balancing approaches is given first. Based on this, the potentials and challenges of additive balancing methods, which directly apply material to the lamination stack, are explained. In this context, two joining processes, namely ultrasonic welding and laser beam welding, are examined in more detail on the basis of practical experiments. In particular, influences on the quality of the lamination stack are considered.<br
Keywords: balancing; rotor; electric motor production; manufacturing; NVH; laser beam welding; ultrasonic welding

Comparison of Various Manufacturing Processes for Hairpin-Stators with Different Conductor Material - Riedel, Andreas; Kneidl, Maximilian; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (Springer Nature, 2022)
The increasing demand for alternative drives in the mobility sector is continuously generating innovations in the development and production of electrical machines. The automotive industry relies more and more on traction machines with hairpin stators, as the process chain can be automated more easily and the copper filling factor can be increased. Enhancing the electrical copper filling factor in particular allows an improvement of the power density of the electrical machine. However, large conductor diameters lead to additional losses at high frequencies, as they occur in high-speed applications, due to eddy current effects. These operational disadvantages can be avoided by substituting the solid rectangular conductor by a litz-wire. Nevertheless, this semi-finished product requires a more complex manufacturing process. Within this paper the process chain for the production of a litz-wire hairpin-stator is illustrated and the challenges in the process chain of a stranded conductor compared to a solid conductor are presented. In this context, the manufacturing aspects for the production of the litz-wire hairpins are considered in detail.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Copper filling factor; Litz-wire; Process chain

Concept for Magnet Intra Logistics and Assembly Supporting the Improvement of Running Characteristics of Permanent Magnet Synchronous Motors - Meyer, Alexander Wilhelm; Heyder, Andreas; Kühl, Alexander; Sand, Christian; Gehb, Hermann; Abersfelder, Sandra; Franke, Jörg; Holzhey, Rocco; Buettner, Ulrich; Wangemann, Sebastian (Procedia CIRP, 2016)
Current scientific studies prove the dependency of the running characteristics of permanent magnet synchronous motors on variations of the physical properties of permanent magnets and manufacturing errors. Currently, this fact is not considered in most process chains for magnet and rotor assembly. Thus, insufficient rotor quality can only be detected during the end-of-line test, causing rejects of whole motors. As a solution for these drawbacks, a computerized magnet intra-logistics storage and assembly concept is presented, using sophisticated magnet measurement technologies. This concept allows for the traceability of single magnets and enables to compensate variations of the magnetic properties by selective magnet assembly.
CRIS-Team Scopus Importer:2023-03-07
Keywords: magnet assembly; magnetic tolerancing; PMSM; tolerancing; traction drives

Continuous Improvement of the Screen printing Process of Magnetic Sheets for Electric Machines by Statistical Design of Experiment - Schmidt, Alexander; Wieprecht, Nico; Thamm, Julian; Kühl, Alexander; Franke, Jörg (Lecture Notes in Mechanical Engineering, 2023)
Electric machines are an essential element to the electrification of industry and mobility for achieving a sustainable economy. Particularly important are the resource-efficient production of stator and rotor sheet packages and the reduction of iron losses during operation. The screen printing technology enables the production of very thin magnetic sheet laminations in near net shape geometry and thereby minimization of material waste in production. Simultaneously the efficiency of electric motors in use will be increased by reduced eddy current and hysteresis losses due to decreasing sheet thickness and avoided mechanical stress in the manufacturing process. In addition, screen printing enables multi-material components and variable alloy compositions. This paper presents the requirements of the screen printing process for magnetic sheets and identifies the relevant influencing factors and printing parameters to achieve the product specifications in multiple iterations and using universal statistical design of experiments methods. The target parameters investigated are cycle-time, green part weight, roundness, and layer thicknes
Keywords: Additive Manufacturing; Electric Motor; Magnetic Sheets; New Materials; Resource-efficient Production

Design and Validation of an Inline Curvature Measurement for Flat Wire Straightening in Hairpin Stator Production - Preitschaft, Anja; Baader, Marcel; Mayr, Andreas; Bader, Thomas; Franke, Jörg; Kühl, Alexander (2024 14th International Electric Drives Production Conference (EDPC), 2024)
This paper presents a novel inline sensor-based method for measuring the curvature of straightened flat wires during hairpin stator production. The accurate control of the wire curvature is essential to ensure precise alignment in subsequent assembly steps. Existing methods for curvature assessment often rely on an external measurement in dedicated metrology stations or subjective visual inspection, both of which have significant limitations in terms of accuracy, consistency and time efficiency. The inline method proposed in this work offers a promising alternative that enables continuous, high-precision curvature measurement immediately after the straightening process. To evaluate the feasibility of the system, an experimental study is conducted in which straightened wire samples are analyzed using both the developed inline sensor system and an offline 3D optical profilometer as a reference. The results are then compared to determine the suitability and the accuracy of the inline measurement technique for industrial applications. The results indicate that the inline system provides reliable curvature measurements, demonstrating its potential to significantly improve quality control, reduce scrap and increase the overall efficiency of wire straightening processes in electric motor productio
Keywords: electric motor production; hairpin technology; straightening process; curvature measurement

Design, Construction, and Laser Welding of a Contact Ring for Automated and Reliable Coil Connection for Wound Power-Dense Flat Wired Stators - Vogel, Alexander; Baader, Marcel; Wirthmann, Felix; Kühl, Alexander; Franke, Jörg; Kassel, Florian (2024 IEEE 69th Holm Conference on Electrical Contacts (HOLM), 2024)
In the manufacturing of electric motors, the stator is the most expensive component of the electric motor. For this reason, the stator is very interesting in terms of automation and offers various possibilities for increasing production efficiency. In addition to some process steps that are already highly automated, others are still largely manual. These mainly include work steps in the area of insulation assembly or contacting. In both cases, the flexible behavior of the free wire ends poses a major challenge and can only be achieved with great effort or, in the case of large quantities, by machines or robots. Especially in compact and therefore extremely power-dense drives that are not based on hairpin technology, the process of contacting the individual coils must be redesigned. To reduce the complexity of handling the free ends, the substitution of a conventional, manual crimping process through the use of a contact ring, in conjunction with a laser-assisted contacting process, can be a promising approach. This issue will be pursued as part of this scientific work and the feasibility of such geometries in interaction with laser contacting will also be demonstrated for flat wire stator
Keywords: Coils; Contacts; Welding; Production; Stators; Ring lasers; Reliability engineering; Wire; Robots; Electric motors; electric drives; stator production; contact ring; contacting; laser welding

Development of Magnetic Sheets for CO2 Efficient Electric Drives Using an Additive Manufacturing Approach - Schmidt, Alexander; Ziegler, Marco; Franke, Jörg; Kühl, Alexander (Lecture Notes in Mechanical Engineering, 2023)
Climate change and its negative consequences for the environment are the greatest challenge of the current era. Electric machines are considered key both for the generation of regenerative electricity and as a substitute for fossil fuels in industry and fossil engines in the transportation sector. Resource-efficient manufacturing and operation of electric machines are therefore of high importance. The central component of every electric machine is the soft magnetic core. The manufacturing process and material selection are influencing the iron losses during operation. This paper presents a novel technology for manufacturing magnetic sheets and lamination cores for carbon dioxide efficient electric drives using an additive manufacturing approach. The potential of the technology is explained and the challenges in process development are highlighted.
CRIS-Team Scopus Importer:2023-07-14
Keywords: Additive Manufacturing; Electric Motor; Electrical Steel; Magnetic Sheets; New materials; Sustainable Manufacturing

Development of Magnetic Sheets for CO2 Efficient Electric Drives Using an Additive Manufacturing Approach - Schmidt, Alexander; Ziegler, Marco; Kühl, Alexander; Franke, Jörg (Springer Science and Business Media Deutschland GmbH, 2023)
Keywords: Magnetic Sheets; New materials; Electric Motor; Electrical Steel; Sustainable Manufacturing; Additive Manufacturing

Digital Twin of the Linear Winding Process Based on Explicit Finite Element Method - Weigelt, Michael; Kink, Julian; Mayr, Andreas; von Lindenfels, Johannes; Kühl, Alexander; Franke, Jörg (2019 9th International Electric Drives Production Conference (EDPC), 2019)

Effects of Insulation Residues on the Contacting Process of Copper Flat Wire Connections - Kühl, Alexander (2022 IEEE 67TH HOLM CONFERENCE ON ELECTRICAL CONTACTS (HLM), 2022)
CRIS-Team WoS Importer:2023-02-10

Electric Motor Production 4.0 – Application Potentials of Industry 4.0 Technologies in the Manufacturing of Electric Motors - Mayr, Andreas; Weigelt, Michael; von Lindenfels, Johannes; Seefried, Johannes; Ziegler, Marco; Mahr, Alexander; Urban, Nikolaus; Kühl, Alexander; Hüttel, Franziska; Franke, Jörg (8th International Electric Drives Production Conference (EDPC), 2018)

Electric Propulsion Units in aviation - approach for a mechanical permanent magnet rotor design and the related manufacturing concept - von Lindenfels, Johannes; Ihne, Thorsten; Franke, Jörg; Kühl, Alexander (2022 12th International Electric Drives Production Conference, EDPC 2022 - Proceedings, 2022)
Electric propulsion units are key components for hybridization and electrification of aviation enabling decarbonization and emission reduction. This application is characterized by significant requirements regarding reliability and power density. This paper deals with a specific mechanical rotor design for Electric Propulsion Units configured as Halbach array and its related manufacturing process. First, existing rotor configurations of electric propulsion units are discussed. Based on this analysis optimization potentials regarding air gap minimization, cooling and retaining of centrifugal forces are introduced. The derived reference design compromises a modular setup of the magnetic active part including combinations of form fit and adhesive bond for all relevant interfaces. The individual advantages and disadvantages of the design as well as further optimization potentials are evaluated based on simulative and experimental investigations. The selected design correlates with a specific assembling and magnetization process which is also discussed. Due to a high number of single parts the assembling is performed as multistage process. The magnetization is conducted applying a sub-assembly strategy to avoid manufacturing problems. Finally, an outlook is given with focus set on the aviation compliant certification process.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electric motor production; Electric Propulsion Units; Halbach Array; sub-assembly magnetization

Electromagnetic Actuators Suitable for High Temperatures Using Thin Aluminum Foil as Conductor - von Lindenfels, Johannes; Qomi, Mohammad Pahlevani; Utsch, Daniel; Franke, Jörg; Kühl, Alexander; Reibenweber, Lukas; Stadler, Alexander (2022 12th International Electric Drives Production Conference, EDPC 2022 - Proceedings, 2022)
Electromagnets are widely used as drive elements in many technical areas, e.g. as control elements for valves. The technical requirements include, for example, static and dynamic electromagnetic properties, compact design and reliability. On the economic side, the total costs must be considered. Copper (Cu) is predominantly used as a conductor material for electromagnets. However, this is problematic due to the fluctuating market prices of the metal. For example, the raw material prices for Cu have doubled somewhat between 2016 and 2022. In this paper, as an alternative to coils made of round Cu wire, options are sought for producing coils from anodised aluminum (AI) foil. For this purpose, the advantages and disadvantages of round Cu wire and Al foil are discussed with regard to material properties, manufacturing processes and handling. First, technical concepts for the realisation of this replacement are reported. Then the cylindrical coil is manufactured from anodised Al coil and a prototype of a cylindrical coil is built for demonstration. The newly manufactured coils are tested against the conventional coils made of Cu and the results of the comparison are presented.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Al2O3; aluminum foil; anodized aluminum; filling factor; solenoid; winding technology

Energy efficient processes of electric motor manufacturing - Kühl, Alexander; Kreitlein, Sven; Höft, Annika; Franke, Jörg (2018 IEEE Texas Power and Energy Conference (TPEC), 2018)

Evaluation of different methods for removing the conductor insulation of stranded conductors - Riedel, Andreas; Hahn, Roman; Kühl, Alexander; Franke, Jörg (12th International Symposium on Advanced Topics in Electrical Engineering, ATEE 2021, 2021)
The ecological change in society and politics leads to an increased demand for alternative drives. In the field of mobility, this can be observed by ongoing innovations in research and development as well as in the production of electric machines. Currently, the automotive industry is focusing more and more on traction drives using hairpin technology. The reasons for this are the easier automation of the manufacturing process and the higher copper filling factors that can be achieved. The latter help to improve the power density. At high frequencies, which inevitably occur in high-speed applications, large conductor dimensions lead to additional losses due to eddy currents. To reduce these losses, twisted round wires can be used instead of flat conductors. Nevertheless, the manufacturing as well as the processing of this semi-finished product is more complex. The aim of this paper is to present and compare the possibilities for removing the required tape of the stranded conductor and to substantiate it with initial results. For this purpose, the general production chain of a hairpin stator is explained at the beginning of the paper in order to show the reasons why the removal of the bandage is of elementary importance. This is supplemented by technological aspects of stranded wire technology which cause-effect relationships serve as the basis for the main part of this paper.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Electric traction drives; Hairpin winding; Insulation material; Litz wire; Skinning methods; Stranded conductors

Evaluation of economic and ecologic potential of induction heating in the context of insulation systems within electric drives - Hofmann, Benjamin; Spreng, Simon; Kühl, Alexander; Franke, Jörg (IEEE Electrical Insulation Conference, 2015)
Resin applications have always been found within the production of electric drives. Replacing natural materials like tar and rubber, industrial produced polymers quickly spread amongst all major components and manufacturing steps of electric machines. Today, thermosetting resins are mainly used within the disciplines of insulation and fixation of materials, manifesting in wire enamels, impregnation varnishes, potting resins and thermally curing adhesives. Numerous variations in topology create various challenges around these products. Thermal curing generally uses an excessive amount of energy when being conducted by oven heating or infrared radiation. Alternative and particularly energy-efficient technologies are available, but have yet to be investigated from a scientific perspective. Within the research project E vertical bar Solation, the E vertical bar Drive-Center at the institute FAPS of the Friedrich-Alexander-University of Erlangen-Nuernberg has aimed to investigate induction heating technology as an energy-saving method for thermosetting resin and powder coat curing to create insulating layers within an automated and flexible production of electric drives. Saving potential in the context of electrical sheet laminations has shown to be as high as up to 95% of electrical energy. In order to determine the value of this technology, simulative as well as empiric investigations have to be made to create a better understanding of how induction heating of sheet lamination works and to determine feasibility and integration into current production processes. The paper will present the latest outcomes of energy-focused value stream methods in order to determine applicable scenarios and production thresholds, in which induction heating can be a viable alternative to current heating technologies. In parallel, a simulative approach is under development to determine temperature distribution during heating process of laminated cores. The project aims for an extensive and fundamental knowledge of the process itself in order to determine optimal heating times and maximum efficiency.
Keywords: insulation; resin; induction heating

Evaluation of Laser-welded Electrical Steel Laminations for Electric Motors - Ziegler, Marco; Brandl, Florian; Kühl, Alexander; Franke, Jörg (12th International Symposium on Advanced Topics in Electrical Engineering, ATEE 2021, 2021)
The soft magnetic core is a basic component in electric motors, along with the winding and insulation systems. Soft magnetic cores are continuously magnetized and demagnetized to guide and amplify the magnetic flux. To reduce iron losses during operation, stator and rotor cores are usually made of thin laminated iron-silicon sheets insulated electrically from each other. These materials are easy to process (cutting, joining etc.), the costs are low, and the magnetic as well as the mechanical properties are adjustable during production. Due to the increasing requirements for electric motors for automotive sector, the material grades and corresponding manufacturing processes have been even optimized. For the production of Fe-Si laminations, the single sheets are stacked and joined. For this purpose, laser beam welding is increasingly used, especially in the series production of larger stators. However, the welding process affects the microstructure in the heat-affected zone and creates an electrically conductive connection between the single sheets. This increases the production-related iron losses, which have to be considered already in the design of the electric machine. As part of this research paper, the impact of laser welding of Fe-Si electrical steel sheets on the electromagnetic properties is analyzed and relationships are derived. This makes it possible to consider the production-related impact factors at an early stage.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Electric drives production; Electrical steel laminations; Iron losses; Laser welding; Soft magnetic materials

Experimental Evaluation of Tool Geometries for the Ultrasonic Crimping Process for Tubular Cable Lugs - Seefried, Johannes; Gläßel, Tobias; Kühl, Alexander; Mayr, Andreas; Franke, Jörg (2019 IEEE Holm Conference on Electrical Contacts, 2019)
In the production chain of electric drives, the electrical and mechanical contacting of the winding ends with a contact element is a time-consuming and cost-intensive process step. The most common processes, e.g., hot crimping, are characterized by high tool wear and enormous energy consumption. An innovative and at the same time energy- efficient process is the ultrasonic crimping process which also combines the two process steps of skinning and contacting in a single process. The thermal energy required for skinning is based on the damping of oscillation energy in the cable lugs used. Due to the direct heat generation in the cable lug and the oscillations coupled in, the process has high potentials with regard to process stability, contacting of high-frequency litz wires and energy consumption. However, some disadvantages like the occasional occurrence of fatigue fractures in the tubular cable lugs and unclear dependencies reducing process reliability have to be investigated. One possibility to avoid the cracks and to further increase the process stability of ultrasonic crimping is the evaluation of adapted tool geometries. In the context of this paper, different sonotrode and anvil geometries are compared and evaluated with regard to electrical, mechanical and visual connection quality.<br

Experimental Investigation of a New Manufacturing Technology for Hairpin Stators with Litz Wires - Riedel, Andreas; Kühl, Alexander; Franke, Jörg; Graf, Rolf; Hubert, Thomas; Bauer, David (2022 12th International Electric Drives Production Conference, EDPC 2022 - Proceedings, 2022)
The increasing demand of electric drives in the mobility sector leads to continuous innovations in the development and production of electric machines. Currently, it can be seen that hairpin technology is well established in the automotive industry for traction drives. In addition to the high level of automation of the process, the reasons therefore are the achievable copper filling factors, which result from the flat conductors used and thus increase the power density of the electrical machine. However, at higher frequencies, as a result of higher driving speeds, large conductor dimensions, especially the height of the conductor, lead to undesirable aspects in the form of eddy current losses. These negative effects can be reduced by replacing the solid rectangular conductor with a stranded conductor. Therefore, the substitution of the conductor material in the field of hairpin technology can be classified as the next innovation stage. The base material is a twisted stranded conductor compacted into a rectangular shape. In this paper, a novel process chain for the manufacturing of a stranded hairpin stator is presented, individual process steps are analyzed and potential improvement measures are explained. Subsequently, an evaluation is made on the basis of an assembled and electrotechnically measured stator with stranded hairpins.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electric traction drives; hairpin winding; litz-wire; stator manufacturing; stranded conductors; wire materials

Experimental Setup of a Process Chain for Contacting Litz Wires for Electrical Drives - Riedel, Andreas; Seefried, Johannes; Schmidt, Alexander; Kühl, Alexander; Franke, Jörg (30th International Conference on Electrical Contacts, ICEC 2020 - Proceedings, 2021)
The main objective in the development of electric drives is the continuous effort to increase the performance. One possibility to achieve this is the use of shaped litz wires. However, shaped litz wires present major challenges regarding the contacting process. In the preparation of the contacting process, the individual conductors of the litz wires must be completely stripped without residues and brought into a defined geometry. This preliminary process step is also known as compacting. The compacting process is the basis for the subsequent contacting of the litz wires with each other or with contact elements. One process for contacting the litz wires is laser beam welding. In the context of this publication, the process chain consisting of ultrasonic compacting and laser beam welding is evaluated. The focus is put on the possible variations of the litz wire topologies, which differ in single wire diameter, number of wires and degree of insulation. Depending on this, parameters for the two processes are elaborated. To evaluate the results, electrical and mechanical testing of the litz wire connections is carried out. In addition, different approaches for the qualification of the compaction quality, in particular the evaluation of insulation residues, are considered.
CRIS-Team Scopus Importer:2023-03-07

Flexible Automatisierung der Statorenmontage mit Hilfe einer universellen ambidexteren Kinematik: Dissertation - Kühl, Alexander (Meisenbach, 2014)
Die fortgeschrittene Globalisierung stellt auch die Branche des Elektromaschinenbaus vor die große Herausforderung, in einem Land mit hohem Einkommensniveau global wettbewerbsfähig zu produzieren. Um die Wertschöpfung nachhaltig im Land halten zu können, ist für die Hersteller elektrischer Antriebe die Entwicklung kundenorientierter Produkte sowie effizienter und innovativer Montageprozesse entscheidend. Ziel der vorliegenden Arbeit war daher die Konzeption dieser Prozesse unter dem Fokus der Flexibilität der Produktionsmittel. Die Montage von Wicklungen und Deckschiebern mit Hilfe einer dualarm- Roboterkinematik, die Einordnung des entwickelten Montagesystems sowie die Konzeption der übrigen Prozessschritte bildeten die Schwerpunkte. Bestehende Montagesysteme zur Produktion elektrischer Antriebe zeichnen sich entweder durch eine sehr starre Automatisierung oder viele manuelle Tätigkeiten aus. Da Vorrichtungen automatisierter Linien auf bestimmte Statortypen ausgelegt und trotz der fehlenden Flexibilität sehr kostenintensiv sind, ist die Weiterverwendung manueller Hilfsmittel für robotergestützte Montagezellen deutlich zielführender umzusetzen. Die gegenüber einer menschlichen Arbeitskraft dem Roboter fehlenden Sinne und kognitiven Fähigkeiten erfordern jedoch eine Anpassung an den Einsatz dieser Hilfsmittel. In diesem Zusammenhang erfolgte im Rahmen der Arbeit zunächst die Konzeption einer Wickelschablone die ohne Kollisionsgefahr von einem Roboter angefahren werden kann. Die entwickelte Drei- Kammern-Schablone stellt eine kostengünstige, zugängliche und schnell zu rüstende Alternative zu universellen Wickelschablonen dar. Nach Erweiterungen besteht ebenfalls die Möglichkeit, die Positionen der Drahtenden festzulegen und damit definiert zu übergeben. Auch bisherige Lösungen, in der Zelle einen Stator definiert zu spannen, erweisen sich als ungeeignet für eine robotergestützte Montage. Beim Spannen des Blechpakets in eine Vorrichtung, die den Stator während des manuellen Einziehens fixiert, ist es nur mit einem hohen Zeitaufwand möglich, den Stator konzentrisch einzulegen. Die einzelnen Spannzangen wurden daher durch einen Kniehebel ersetzt. Dieser ermöglicht das schnelle Spannen mit definierter Mittelachse und Bezugsebene. Die Flexibilität gegenüber verschiedener Statordurchmesser wird durch kostengünstige, schnell zu rüstende, austauschbare Schalen gewährleistet. Nach der automatisierungsgerechten Vorbereitung der Montagezelle war es möglich, die Prozesskette zur flexiblen Montage von Statoren zu konzeptionieren. Ausgehend von einem nutgrundisolierten Stator ist der erste Prozessschritt die Montage der Wicklung. Die beschädigungsfreie Handhabung der biegeschlaffen Drähte ist hierbei eine der wesentlichen Herausforderungen. Um diese zu realisieren, wurden verschiedene Konzepte erstellt, bewertet und aufgebaut. Bei diesen nimmt der eine Roboterarm die Wicklung aus der definierten Lage in der Schablone der Wickelmaschine auf und positioniert sie in der Statornut. Der zweite Roboterarm unterstützt diesen Einziehvorgang, durch die Handhabung des Gegenwerkzeuges. Beide Konzepte unterscheiden sich in der Anzahl der übertragbaren Spulen. Während der elektromechanische Greifer des ersten Prototypens dafür ausgelegt wurde, Einzelspulen möglichst flexibel einzulegen, werden beim Prototypen des zweiten Konzeptes Spulengruppen mit Hilfe eines Einziehwerkzeuges in den Stator gezogen. Neben der Verkürzung der Prozesszeit ist hierbei v.a. der Kontaktierprozess wesentlich effektiver durchzuführen. Nach der Montage müssen die Wicklungen fixiert und isoliert werden. Bei Versuchen mit ersten Prototypen wurde klar, dass die robotergestützte Montage vormagazinierter Deckschieber v.a. aufgrund der biegeschlaffen Wicklungen innerhalb und außerhalb des Stators nur sehr schwierig zu realisieren ist. Neben den Problemen mit der Zugänglichkeit stellte sich v.a. das Einfädeln und Einschieben des Materials als problematisch dar. Mit der Weiterentwicklung zu einem zweiten Prototyp, welcher Transport, Formgebung, Zuschnitt, Zuführung und Einschieben der Deckschieber aus dem Lieferzustand des Isolierbandes übernimmt, können die Probleme der Zugänglichkeit und des Materialtransportes überwunden werden. Ein drittes Werkzeug umgeht die genannten Probleme durch eine Substitution des Prozesses. Nach ausführlicher Materialrecherche und Auswahl konnte an Stelle des seitlichen Einschiebens eines festen Stoffes ein geeigneter Kleber von oben in die Nut appliziert und mittels UV-Licht ausgehärtet werden. Das System ist flexibel gegenüber des Statortyp, sowie der Anzahl der zu produzierenden Motoren und ermöglicht zudem die Erweiterung um den Prozessschritt der Nutimprägnierung. Für die künftige Weiterentwicklung der Deckschieber-Technologie ist neben der Untersuchung von Prozess- und Materialalternativen auch eine verbundene, detaillierte Analyse der Lebensdauer der Wicklung zielführend. Neben mechanischen, thermischen und elektrischen Einflüssen können hier auch Funktionsmaterialien berücksichtigt werden. Zur Schließung der Prozesskette wurden die folgenden Schritte Kontaktierung und Wickelkopfformen konzeptioniert. Die vorgestellten Werkzeuge ermöglichen das schaltrichtige Einsammeln der freien Wicklungsenden sowie die Zuführung zu einer Heißcrimpanlage. Die Integration des Kontaktierprozesses in ein robotergeführtes Werkzeug ist aufgrund der spezifischen Prozessparameter, der hohen Ströme und Spannungen nur bedingt sinnvoll. Ebenfalls nicht ohne zusätzliche Werkzeuge und Aktoren kommt das Wickelkopfformen aus. Aufgrund der hohen Prozesskräfte übernimmt der Roboter lediglich die Handhabung der Werkzeuge. Die Prozesskräfte werden über einen linearen Pneumatikaktor auf ein Werkzeug übertragen, welches durch seinen komplexen geometrischen Aufbau diese nutzt, um die Wicklung axial und radial zu komprimieren. Die vorgestellten Prozesse wurden zu einem Montagesystem projektiert. Im Fokus stand hierbei, Prozesse - wenn möglich - zu parallelisieren und nur - wenn nötig - mit einer Kooperation der beiden Roboterarme abzuarbeiten. Das System wurde im Rahmen der Arbeit simulativ untersucht. Neben der Offline-Programmierung stand hierbei v.a. die Systemoptimierung durch eine Ablaufsimulation im Vordergrund. Es wurden kritische Prozessschritte, wie die zeitintensive Montage der Deckschieber durch einen Roboterarm, detektiert und Maßnahmen, wie die Erweiterung um eine zweite Wickel- und Roboteranlage vorgeschlagen, die zu einer Effizienzsteigerung des Systems führen. Die Analyse der Wirtschaftlichkeit und der Prozesszeiten sowie der qualitative Vergleich der Prozessschritte validiert die Zelle mit einem resultierenden Einsatzszenario. Hierbei kann nachgewiesen werden, dass ein flexibel robotergestütztes Montagesystem, wie in dieser Arbeit konzeptioniert, bei einer jährlichen Produktion in mittleren Stückzahlen wirtschaftlicher arbeitet als eine manuelle oder vollautomatisierte Linie. Innerhalb der vorliegenden Arbeit wurden Technologien, Prozesse und Systeme aufgezeigt, die eine effiziente und flexible Montage von Elektromotorstatoren ermöglichen. Für eine Umsetzung in einer industriellen Umgebung müssen jedoch einerseits die konzeptionierten Werkzeuge weiterentwickelt, andererseits auch die Technologien unternehmensexterner Partner (Kontaktierung) flexibler gestaltet werden. Eine wichtige Voraussetzung für die Industrialisierung der Prozesse im nächsten Schritt ist die steuerungsseitige Weiterentwicklung und der Einsatz von CAD/CAM-Ketten über die gesamte Prozesskette. Nach Erfüllung aller Rahmenbedingungen sind die Potentiale, wie eine schnelle Programmierung der Anlage und der Werkzeuge sowie Rückschlüsse auf die montagegerechte Konstruktion von Statoren, enorm. Ebenfalls wichtig ist die Optimierung moderner Sensoriksysteme. Eine prozesssichere Detektion von Objekten mit kleinen geometrischen Abmessungen ermöglicht durch eine CAD/CAM-Kopplung neben der Korrektur von Montagefehlern auch das Greifen von freien Spulen- oder Wicklungsenden. Nach einer erfolgreichen Einführung und Umsetzung der robotergestützten Prozesse als Alternative zur manuellen oder automatisierten Prozesskette eröffnen sich für den Produzenten elektrischer Antriebe deutliche Potentiale zur Steigerung der Produktionsflexibilität und -effizienz.

Functionally integrated additive manufactured rotor components for torque-dense aircraft electric motors - von Lindenfels, Johannes; Posch, Dennis; Ihne, Thorsten; Franke, Jörg; Kühl, Alexander (Procedia CIRP, 2023)
In dealing with emissions targets worldwide, fundamental questions about the future arise for commercial aviation. The resulting consequences for aviation require efforts to make air traffic CO2 neutral. In this context, electrification is an important building block to enable the aviation industry to provide transport in the future with increasing traffic volumes. To achieve this goal, electric motors for flight operation must have a high power and torque density and operate as energy-efficiently as possible. The PM synchronous motors predominantly proposed for such applications have above average efficiencies but could provide higher peak powers if they could be thermally more loaded. In particular, the sensitive permanent magnets lose efficiency as the operating temperature of the electric motor increases, reducing the maximum possible torque of the motor. Since conventional rotor construction methods limit the design, additive manufacturing is used to develop a rotor design that allows the rotor magnets to be cooled in close range to their contours. In addition, by selective laser melting mechanical, thermal, and magnetic functions are integrated. A process for hybrid manufacturing of novel rotor topologies is proposed. For this purpose, the rather conventional rotor topology is replaced by an additive function-integrated component for a reference electric motor. By means of an FEM analysis, it was shown that the mechanical strength of the alternative fixation method is maintained. Using adequate design guidelines, the AM structural components were fabricated in aluminum and an iron-nickel alloy and the permanent magnets were secured on it using 1K-epoxy adhesive. CFD analysis was used to simulate the flow conditions and heat transfer to the coolant in the internal structures of the AM components. Finally, the effect of the integrated cooling function was verified with an experimental setup. The results show that the torque influencing factor of the magnetic induction can be increased.<br
Keywords: Additive manufacturing; PMSM; Electric aviation; Magnetics; cooling system; Halbach array

Hot crimping through innovative inductive heating in the production of electric motors - Kühl, Alexander; Zitzelsberger, Maximilian; Seefried, Johannes; Masuch, Michael; Miller, Tim; Franke, Jörg (2019 IEEE International Electric Machines and Drives Conference, IEMDC 2019, 2019)
In electrical machine production, the coil ends of the winding must be electrical contacted in the correct phase. The hot-crimping process is a commonly used method for joining the enameled copper wires to a cable lug in one process step. However, due to its working principle, this technology has the strong disadvantage of high tool wear, which leads to frequent maintenance. In this paper, an improved hot crimping method is presented to overcome this detriment. Therefore, inductive heating is used to strip the wires and the tools for crimping are made of a nonconductive technical ceramic.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Contacting; Electric drives production; Hot crimping; Inductive stripping; Winding

Implementation of the Needle Winding Technique for Diamond Coils - Bickel, Benjamin; Mahr, Alexander; Kühl, Alexander; Franke, Jörg; Meixner, Sebastian; Berendt, Emil; Riedel, Andreas (5th International Electric Drives Production Conference, 2015)

Improving the Inductive Crimping Technology in the Production of Electric Motors - Kühl, Alexander; Franke, Jörg (2021 IEEE SIXTY-SIXTH HOLM CONFERENCE ON ELECTRICAL CONTACTS (HLM), 2021)
CRIS-Team WoS Importer:2022-05-13

Influence of Cable Lug Properties on the Torsional Ultrasonic Crimping Process of High-Frequency Litz Wires - Seefried, Johannes; Wieprecht, Nico; Franke, Jörg; Kühl, Alexander (2023 13th International Electric Drives Production Conference, EDPC 2023 - Proceedings, 2023)
The growing popularity of electromobility requires a continuous development of the associated charging infrastructure and the charging technologies used. Inductive charging systems, which enable a wireless power transfer (WPT) in the static and dynamic state of the electric vehicles, bear a great potential in this context. WPT is based on a ground coil and a coil on the vehicle side. The coils consist, among other components, of high-frequency litz wires, which are characterized by a high number of primary-insulated and stranded individual wires. During the production of the coil systems, this results in a wide range of challenges, especially for the contacting technology of the high-frequency litz wire. Thus, all individual wires of the litz wire must be stripped and electrically as well as mechanically terminated with contact elements. One of the processes used for this step is hot crimping, where the litz wires are crimped with tubular cable lugs and the primary insulation is thermally removed by resistance heating. Another process that has not yet been used in industrial series production is the torsional ultrasonic crimping process, which offers particular advantages in terms of process energy consumption. In order to further optimize this process, the influence of the tubular cable lugs used on the contact quality and various process variables is therefore analyzed in the context of this publication. The main focus is on the surface properties of the cable lugs.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Litz Wire; Ultrasonic Crimping; Ultrasonic Welding; Wireless Power Transfer

Influence of Enameled Wire Preparation on the Laser welding of Hairpin Windings - Gläßel, Tobias; Riedel, Andreas; Franke, Jörg; Kühl, Alexander (2022 IEEE 67TH HOLM CONFERENCE ON ELECTRICAL CONTACTS (HLM), 2022)
CRIS-Team WoS Importer:2023-02-10

Influences of joining process parameters on stator and rotor cores for electric drives - Ziegler, Marco; Biburger, Michael; Kühl, Alexander; Franke, Jörg (2019 16th Conference on Electrical Machines, Drives and Power Systems, ELMA 2019 - Proceedings, 2019)
Due to the rising demand for high-efficiency electric drives, the requirements for production processes are also increasing. The process steps have a significant effect on product quality and efficiency of the electric machine. In this paper, the joining processes for stator and rotor lamination stacks i. e., interlocking, laser welding, bonding and bonding varnish are compared in a holistic evaluation process. For this purpose, practical joining tests with varying process parameters on basis of a toroidal core are carried out. In this context, the process behavior and energy demand during manufacturing are evaluated. Mechanical and electromagnetic tests are used to determine the influence of the joining parameters on product quality and electromagnetic losses. The investigations were intended to support the later development of new complex processes for electric drives.
CRIS-Team Scopus Importer:2019-08-20
Keywords: Electromagnetic losses; Joining processes; Mechanical tests; Stator and rotor cores

Influencing Factors for the Ultrasonic Compacting Process of Insulated Litz Wires for Electric Drives - Seefried, Johannes; Riedel, Andreas; Lohbauer, Andreas; Baessler, Hendrik; Kühl, Alexander; Franke, Jörg (30th International Conference on Electrical Contacts, ICEC 2020 - Proceedings, 2021)
The increasing demand for new electric drive concepts in the automotive sector leads to innovations in the development and production of these drives. Due to the demand for steadily higher drive speeds, litz wires, also called stranded wires, offer various advantages in terms of loss reduction. These losses include current displacement due to the skin- and proximity effect in the wire at higher frequencies. However, these litz wires complicate the process step of contacting the winding ends. For example, during this contacting process it is necessary to connect a high number of individual wires electrically conductively and mechanically with each other. However, these individual wires must be stripped simultaneously during the process. One possibility to implement this process step is the ultrasonic compaction process. By applying and damping ultrasonic oscillations, the individual wires can be thermally stripped and also welded together. However, a wide range of influencing parameters must be validated for this process. These include relevant process parameters as well as properties of the litz wires used. Among other things, the properties can be divided into the type of insulation, the number of individual wires and their diameter. Within this publication, the essential process parameters are identified and evaluated in terms of the quality of the compaction by using suitable methods for measuring the node resistance.
CRIS-Team Scopus Importer:2023-03-07

Infrared laser based contacting of bar-wound windings in the field of electric drives production - Gläßel, Tobias; Baat, Florian; Schwinghammer, Daniel; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (Procedia CIRP, Volume 74, 2018)
Driven by electric mobility innovative winding methods increasing the copper fill ratio and thus the power density of electrical drives gain in importance. Compared to conventional windings, bar-wound windings based on rectangular cross sections besides optimized copper fill ratios also offer advantages in terms of automated production. Because of the high number of joints necessary for the manufacturing of the winding, contacting efforts increase significantly wherefore the process of laser welding, due to its short process times and high reproducibility shows potentials to realize the process step. This paper examines the most important interactions within the process of laser welding of insulated copper wires with rectangular cross sections in the context of electric drives production. Besides workpiece specific factors, the focus is set on process parameters, beam guidance strategies and specific quality requirements. For this purpose, a parameter study based on design of experiments is executed in which suitable measuring technologies are used to quantify the properties of the samples. <br
Keywords: laser beam welding; infrared lasers; insulated copper conductors; hairpin windings; electrical contacts

In-line Measurement Techniques of Resin-based Insulation Processes for Wireless Power Transfer Systems - Kneidl, Maximilian; Benke, Daniel; Masuch, Michael; Kühl, Alexander; Franke, Jörg (2021 IEEE Conference on Electrical Insulation and Dielectric Phenomena (CEIDP), 2021)
The increasing demand for electric mobility is continuously generating innovations in the development and production of electrical machines such as wireless power transfer (WPT) systems. Therefore, new insulation resins with different filler types are investigated in detail to prevent electrical breakdowns and to increase the thermal conductivity of the whole insulation system. In contrast to the development and optimization of new materials, the application technology, process control and testing still remains largely unchanged. As a result, the transfer of the optimized material properties of new insulation resins to the specific component properties is restricted. In the worst case, this leads to an inappropriate processability of the resin and subsequently to the failure of the electrical machine. Furthermore, end-of-line tests only allow a qualification of the final insulation system after impregnation and curing. Thus, defective components can only be identified and discarded or repaired at the end of the process chain, which causes additional costs in production. The aim presented in this work is to identify and measure the dielectric properties of the insulation material along the encapsulation process of a coil structure for WPT systems, to derive information about the overall quality of the insulation system. Therefore, a test setup for qualifying the insulation system capability during the encapsulation process will be elaborated. The results of the in-line measurements are then validated with partial discharge measurements and micrographs of the conductor structur

Innovationen für die Elektromotorenproduktion von morgen: Von neuen Prozesstechnologien, Automatisierungslösungen bis hin zu Industrie 4.0-Ansätzen - Mayr, Andreas; Masuch, Michael; Kühl, Alexander (Automobiltechnologie in Bayern + e-Car, 2019)

Innovations for the electric motor production of tomorrow: From new process technologies, automation solutions through to Industry 4.0 approaches - Mayr, Andreas; Masuch, Michael; Kühl, Alexander (Automobiltechnologie in Bayern + e-Car, 2019)

Innovative Assembly of Stators using Ambidextrous Kinematics - Kühl, Alexander; Franke, Jörg (WCECS 2015 - World Congress on Engineering and Computer Science 2015, 2015)
Keywords: E|DRIVE; Motor; Electric Motor; Robot

Innovative developments for automated magnet handling and bonding of rare earth magnets - Franke, Jörg; Tremel, Jan; Kühl, Alexander (2011 IEEE International Symposium on Assembly and Manufacturing, ISAM 2011, 2011)
Keywords: Assembly; Handling; Bonding; Permanent Magnet

Innovative processes and systems for the automated manufacture, assembly and test of magnetic components for electric motors - Franke, Jörg; Dobroschke, Andreas; Tremel, Jan; Kühl, Alexander (1st International Electric Drives Production Conference, EDPC-2011, 2011)
Keywords: Coil Winding; Automated Assembly; Robotic Assembly; Permanent Magnet Assembly

Insulation Thickness Measurement in Hairpin Stator Production Using a Confocal Chromatic Line Sensor - Preitschaft, Anja; Baader, Marcel; Wagner, Gerald; Franke, Jörg; Kühl, Alexander (Proceedings of the Conference on Production Systems and Logistics: CPSL 2025, 2025)
The insulation thickness of enameled flat wire is a critical parameter in electric motor production based on hairpin technology, directly affecting key manufacturing processes such as straightening, bending, stripping and welding. Adapting these processes based on accurate insulation measurements can significantly improve production efficiency and reduce scrap. This paper presents an inline confocal chromatic line sensor designed to measure the insulation thickness of polyamide-imide (PAI) coated flat wires. Unlike conventional point-based sensors, this advanced system measures a 1.8 mm line, capturing insulation thickness data over a wider range and providing comprehensive insight into wire properties. To investigate the applicability of this line sensor for the use case at hand, the measurement system is integrated into a hairpin production line before the straightening process, providing real-time measurements of the insulation thickness of the raw material prior to further processing. The sensor is first calibrated to determine its optimum operating range. A series of inline measurements are then taken and microsections of the measured wire samples are analyzed using a laser microscope to obtain ground truth values. The comparison between the inline and the offline measurements shows high accuracy, confirming the feasibility and reliability of the sensor for the application at hand. This study highlights the potential of confocal chromatic line sensors as a powerful tool for inline insulation thickness measurement, offering opportunities to optimize electric motor production processes such as straightening, bending, stripping and welding. The integration of such sensors into hairpin stator production lines represents a significant step towards data-driven process optimization, improving process quality, sustainability and efficienc
Keywords: Electric Motor Production; Hairpin Technology; Enameled Copper Wire; Insulation Thickness; Confocal Chromatic Sensor

Investigation of Insulation Layers on Additive Manufactured Electrical Steel Laminations in Electric Motors - Ziegler, Marco; Schafer, Paul; Wieprecht, Nico; Franke, Jörg; Kühl, Alexander (IEEE Transactions on Dielectrics and Electrical Insulation, 2023)
In this paper, the insulation properties of printed electrical steel laminations for high-efficiency electric machines are investigated. In contrast to conventionally produced electrical steel laminations made from rolled coil material, additive manufacturing from powder material allows extremely thin and complex near-net-shape geometries with no scrap material. At the same time, the printed electrical steel laminations offer the advantage that no additional cutting steps are required and specific material characteristics are adjustable which enables special machine modifications. To avoid global eddy current paths between the single sheet layers after the stacking process, the laminations must be insulated from each other in order to keep losses low, especially at high operating frequencies. This requires a sufficiently high surface insulation resistance on the sheets. Since the insulation coating cannot be applied continuously during rolling, as in conventional production, alternative approaches for application are required. The investigations characterize and evaluate potential insulation systems for additive manufactured laminations. The printed sheets are analyzed geometrically, electrically and metallurgically at first and characterized for the next process steps. Afterwards, potential insulation systems are analyzed and investigated in practical tests. The coating systems are characterized in terms of application, thickness, electrical and mechanical insulation properties, and options for further processing. This is crucial as the coating needs a sufficient level of adhesion to the substrate and allows successive bonding.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Core losses; Eddy currents; Electric motors; Electrical insulation; Insulation; Lamination; Lamination; Magnetic cores; Magnetic materials; Metals; Soft magnetic materials; Steel; Three-dimensional printing

Lean 4.0 - A conceptual conjunction of lean management and Industry 4.0 - Mayr, Andreas; Weigelt, Michael; Kühl, Alexander; Grimm, Sebastian; Erll, Alexander; Potzel, Markus; Franke, Jörg (Procedia CIRP, Volume 72, 2018)

Manufacturing influences on transmission efficiency and thermal integration of resonant circuit modules of inductive power transmission systems for electric vehicles - Weigelt, Michael; Jordan, Sophia; Manger, Johanna; Kneidl, Maximilian; Masuch, Michael; Kühl, Alexander; Franke, Jörg (2023 IEEE Wireless Power Technology Conference and Expo, WPTCE 2023 - Proceedings, 2023)
Electromobility is the backbone of modern emission-neutral transportation systems. Wireless energy transfer via induction is the associated complementary technology that significantly improves the user-friendliness of energy supply in various use cases such as static or dynamic wireless power transfer (WPT). The functionality of WPT for electric vehicles is extensively demonstrated, but no automatable manufacturing processes exist to produce them in large scale. Therefore, this paper describes the manufacturing process chain of coil modules of inductive power transfer (IPT) systems and presents quality criteria for these coil systems. Using structured design of experiment (DOE), the manufacturing influences on the quality of the coil modules are presented and quantified. In addition, embedding concepts of the ground assembly (GA) capacitor configuration are qualitatively evaluated.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Assembly; Automotive; E-Road; Inductive Power Transfer; IPT; Production Systems; Wireless Power Transfer (WPT)

Methodical Comparison of Alternative Powertrain Technologies for Long-Distance Mobility Using Germany as an Example - Weigelt, Michael; Mayr, Andreas; Kühl, Alexander; Franke, Jörg (WEVJ (World Electric Vehicle Journal), 2019)
The main barriers to the wide acceptance of electric vehicles, such as the limited driving range or the high acquisition costs, are to be countered by various technology alternatives for the powertrain of the future. Promising developments include improved battery technologies, fuel cell technologies or a constant power supply of the vehicle while driving, for example through dynamic inductive charging. In this context, a holistic technology comparison would contribute to a comprehensive and understandable information situation by making the heterogeneous technological concepts comparable with regard to different evaluation criteria. Therefore, this work describes the basic assumptions of the proposed holistic comparison of alternative powertrain technologies for long-distance mobility. Relevant framework conditions are structured and a procedure for the evaluation of infrastructure expenditures is shown. Building on this, a selection of key performance indicators is defined and explained. The proposed KPI framework is applied to a passenger car in the economic area Germany. The results show that by using electrified roadways, ecological as well as economic advantages against other alternative powertrain designs can be derived.<br

Multi-objective parameter optimization for stacking and sintering of screen-printed magnetic sheets - Schmidt, Alexander; Wieprecht, Nico; Weinrich, Tim; Franke, Jörg; Kühl, Alexander (Production Engineering, 2023)
Screen printing enables the production of very thin magnetic sheet laminations in near net shape geometry. This minimizes material waste in production and simultaneously reduces losses during machine operation and in-creases geometric design freedom. The subsequent sintering process step is particularly relevant, since the geometrical and magnetic properties are defined, and relevant process costs are caused by the heat treatment. This paper presents the requirements of the debinding and sintering process for magnetic sheets and identifies relevant influencing factors to achieve defined product specifications in multiple iterations, using design of experiments. It focuses on the influencing factors furnace atmosphere, sintering temperature, holding time and stacking height and their impact on the magnetic and geometric properties of sintered magnetic sheets.<br
Keywords: Electric motor; Heat treatment; Magnetic sheets; New materials; Sintering; Soft magnetic materials

Numerical Simulation of the Laser Welding Process for Electrical Steel Laminations - Ziegler, Marco; Brandl, Florian; Franke, Jörg; Kühl, Alexander (2022 12th International Electric Drives Production Conference, EDPC 2022 - Proceedings, 2022)
Soft magnetic cores in electric machines conduct and enhance the magnetic flux. The magnetic properties of the single sheets are mainly influenced by the alloying elements, the microstructure and the rolling and annealing process. To reduce eddy current losses during operation, soft magnetic cores are laminated. However, all manufacturing processes and the further assembling steps, like mounting of the stator, change the magnetic properties of the stack. Laser welding is a common method for producing lamination stacks, as very thin sheets can be welded automatically with high velocities. However, the weld seams are electrically conductive connections, which lead to an increase in eddy current losses. Furthermore, the microstructure in the heat-affected zone is impaired, which leads to a higher demand for magnetization and increased hysteresis losses. A main reason for this is the magneto-mechanical effect, as mechanical stresses influence the magnetic properties. For improvement, the process parameters must be adapted to the specific material system and the requirements. In this paper, a numerical simulation model for visualizing and optimizing the heat distribution in welded electrical steel laminations is presented. The main objective is the analysis of the weld dimension for different welding parameters. For this purpose, a transient thermal analysis is carried out with Ansys Workbench. The welding process is mapped in a simplified way with a moving heat source for different conditions. To validate the results, a comparison to experimental tests is applied. In this way, the simulation results are verified and potential sources of errors are identified.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Electrical steel; Finite element analysis; Joining processes; Magnetic losses; Soft magnetic materials

Optimization of the Ultrasonic Crimping Process of High-Frequency Litz Wires by Using Process Data Monitoring - Seefried, Johannes; Schwarz, Elisabeth B.; Bleier, Fabian; Franke, Jörg; Bergmann, Jean Pierre; Kühl, Alexander (2022 12th International Electric Drives Production Conference, EDPC 2022 - Proceedings, 2022)
From a technological point of view, the contacting process of insulated wires to contact elements is one of the most complex steps in electromechanical engineering. To establish an electrical and mechanical connection of winding ends and contact elements, commonly the wire is stripped before the actual contacting process. However, for high-frequency litz wires, consisting of up to several thousand insulated single wires, the stripping process cannot be carried out in advance. Therefore, processes such as hot crimping or ultrasonic crimping, in which the insulation is thermally removed during the crimping process, are used. The latter is characterized by a significantly lower process energy consumption compared to the hot crimping process. It is therefore most attractive for future applications, but process optimization strategies have hardly been addressed in the literature. Within the scope of this publication, several possibilities of optimizing the process of ultrasonic crimping are investigated by means of systematic process data analysis. For this analysis, directly available data from the control system like the required process energy as well as additionally acquired sensor data, such as the sonotrode oscillation, are taken into account and a variation of process control variables as well as the cable lug clamping is conducted.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Data Monitoring; Litz Wire; Ultrasonic Crimping; Ultrasonic Welding; Wireless Power Transfer

Optimized Cutting Process of Flat Wires for Electric Motors with Hairpin Technology - Kühl, Alexander (2023 IEEE International Electric Machines and Drives Conference, IEMDC 2023, 2023)
In order to meet the high demand for electric traction motors in the future, it is advantageous in high-wage countries to automate the production process of electric motors as much as possible and at the same time to streamline it. One suitable technology is the hairpin-stator based electric motor. In this paper, the flexible, robot-based cutting process of hairpin windings is presented, which was developed at the Friedrich-Alexander-Univeristät Erlangen-Nürnberg (FAU). A clean and burr-free cut surface is particularly important for the subsequent joining of the wire into the stator in order to ensure a trouble-free process flow. It is also important to produce a clean cut surface, since the hairpins have to be precisely welded together at this point in order to guarantee an appropriate current flow. Within this publication, the hairpin technology and the associated process chain are first introduced and the specific requirements on the cutting geometry are explained. In the second chapter, the various cutting technologies are presented. In the following chapter, the selected cutting geometries are introduced and the development of the (robot-integrated) fixtures is described. Finally, the test execution and evaluation are shown.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Cutting; Electric Motor; Hairpin; Manufacturing; Rotating Electric Machines; Transportation Applications; Winding

Potentials of few-shot learning for quality monitoring in laser welding of hairpin windings - Raffin, Tim; Mayr, Andreas; Baader, Marcel; Laube, Nadine; Kühl, Alexander; Franke, Jörg (Procedia CIRP, 2023)
For the analysis of high-dimensional data in electromechanical manufacturing, data-driven techniques such as deep learning show great potential. However, the vast amount of required data poses a major barrier to the industrial adoption of said techniques. In the production of electric traction drives, this situation is further exacerbated by short innovation cycles. One of these innovations is hairpin technology, which is increasingly being employed by automotive manufacturers and suppliers. In contrast to classical deep learning approaches, few-shot learning aims at generalizing well despite limited data availability. This makes it ideal for the ramp-up phase of new production technologies for which no large legacy datasets exist yet. Therefore, this paper presents an empirical evaluation of few-shot learning techniques in the context of hairpin stator production. In doing so, we evaluate and benchmark several few-shot learning architectures and traditional approaches for quality monitoring of laser-welded hairpin windings based on image data.<br
Keywords: Few-Shot Learning; Deep Learning; Hairpin Technology; Electric Motor Production; Quality Monitoring; Vision Transformer

Potentials of Optical Coherence Tomography for Process Monitoring in Laser Welding of Hairpin Windings - Baader, Marcel; Mayr, Andreas; Raffin, Tim; Selzam, Jan Harald; Kühl, Alexander; Franke, Jörg (11th International Electric Drives Production Conference (EDPC), 2021)
Optical coherence tomography (OCT) is increasingly being used to monitor and control laser-based welding processes. With the ability to provide pre-, in-, and post-process data, OCT represents a holistic sensor solution for advanced process monitoring and seam tracking. A prospective field of application is the laser welding of rectangular copper wires for so-called hairpin stators as used in electric traction motors. For each stator, a large number of high-quality contact points must be welded in a short cycle time. The quality of a weld not only depends on the laser welding process itself but also on possible manufacturing deviations from upstream process steps. Although OCT seems promising for pre-, in-, and post-process monitoring, no scientific studies exist to date concerning hairpin welding. Starting from a profound presentation of the necessary basics, this paper outlines the potentials of OCT in laser welding of hairpin windings based on first experiments. Regarding pre-process monitoring, it is shown which deviations can be detected by OCT even before the process. Analogously, the post-process monitoring feature can be used to evaluate the resulting weld shape. Further experiments explore whether in-process OCT data can be used to determine the keyhole depth during welding, providing an estimate of the welding depth. The welding of hairpins requires complex beamlines and high focus speeds, which pose high challenges to existing OCT systems. Therefore, the proof is first provided for a simplified welding task before it is performed for the hairpin use case. From the findings gained, the need for action for future research activities is derived, primarily focusing on enabling the OCT -based in-process monitoring for the hairpin welding.<br
Keywords: laser welding; optical coherence tomography; process monitoring; hairpin technology; electric motor production

Potentials of Process Monitoring During Laser Welding of Electrical Steel Laminations - Ziegler, Marco; Mayr, Andreas; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (2019 9th International Electric Drives Production Conference (EDPC), 2019)

Process Development of Screen-Printed Magnetic Sheets for Electric Machines via Statistical Design of Experiments - Schmidt, Alexander; Wieprecht, Nico; Schlichting, Johannes; Denneler, Stefan; Franke, Jörg; Kühl, Alexander (Metals, 2023)
Electrical machines play a major role in achieving a more sustainable economy by driving the further electrification of industry and transportation. To enhance the electric motor productivity during production and the efficiency during operation, it is essential to maximize the material yield rate during the production of stator and rotor sheet stacks and reduce iron losses during operation. Screen-printing technology can help to achieve these goals by producing thin magnetic sheet laminations in near-net-shape geometry, resulting in minimum material waste during production. Moreover, reducing the sheet thickness decreases the eddy current losses and avoids mechanical stress during manufacturing, leading to improved motor efficiency. Additionally, screen printing facilitates the production of multi-material components and variable alloy compositions. This study aims to identify the relevant factors and printing parameters so that screen-printed magnetic sheets can achieve product specifications. A method involving the statistical design of experiments is performed in several iterations to investigate the target parameters of the print cycle time, green part weight, shape integrity and layer thickness, and to analyze the main interdependencies. The results of this study provide valuable insights into optimizing the screen-printing process for soft magnetic sheets, enabling the production of efficient electric motors while reducing material scrap.<br
Keywords: additive manufacturing; electric motor; magnetic sheets; new materials; resource efficient production; screen printing; stator core

Processing influences of resin-based insulation materials for wireless power transfer applications - Kneidl, Maximilian; Masuch, Michael; Rieger, David; Kühl, Alexander; Franke, Jörg (2020 IEEE Conference on Electrical Insulation and Dielectric Phenomena (CEIDP), 2021)
Due to the electrification of the whole mobility sector, the demand for new insulation materials and processes is constantly increasing. Beside the electric traction drives, new technologies such as inductive charging are becoming more and more important in electric vehicles. Especially for wireless power transfer, high-frequency litz wires are used to generate the required electromagnetic field. While semi-finished products and insulation systems are continuously developing, insulation processes like potting remain unchanged. The consequence is an inappropriate insulation of the coil structure resulting in increasing eddy current losses or breakdowns of the inductance. Additionally, high mechanical and thermal loads, occurring in a typical operation environment for electric vehicles, result in accelerated aging of the insulation material. This increases the challenges in the design and manufacturing of insulation systems for inductive power transfer devices. The aim of this work is to identify and evaluate all relevant process parameters for potting high-frequency litz wires with varying primary insulation systems. To ensure the required mechanical and electrical properties, a high degree of impregnation of the litz wires is targete

Process Reliable Laser Welding of Hairpin Windings for Automotive Traction Drives - Gläßel, Tobias; Seefried, Johannes; Masuch, Michael; Riedel, Andreas; Mayr, Andreas; Kühl, Alexander; Franke, Jörg (IEEE International Conference on Engineering, Science, and Industrial Applications (ICESI), 2019)
Keywords: Electric Drives Production; Hairpin Winding; Contacting Technologies

Production Concepts for Inductive Power Transfer Systems for Vehicles - Kühl, Alexander; Kneidl, Maximilian; Seefried, Johannes; Masuch, Michael; Weigelt, Michael; Franke, Jörg (Energies, 2022)
The option of wireless energy transmission in electric vehicles can become the main market driver for electric vehicles due to its distinct advantages, such as range, weight, or costs, over conventional conductive charging solutions. In addition to the great potential, which different research work and realized systems have already shown, there are new requirements for the associated production networks in the automotive industry which must be addressed at an early stage. Furthermore, no solutions currently exist for the industrial production of these components. This paper presents the main components for the feasibility of wireless power transmission in electric vehicles. In addition, the required value chains and processes for the new components of the inductive power transfer systems, and the final assembly for induction coils, which has been developed at the FAU, will be presented. These include the developing of a winding process on a 15-axis special machine, ultrasonic crimping of the litz wire ends, and vacuum potting.<br

Production processes for wireless charging infrastructure. A large-scale market introduction of electric powered vehicles is still opposed by many barriers Produktionsprozesse für kontaktlose Ladeinfrastrukturen: Kosteneffiziente Produktion und Integration von Systemen zur kontaktlosen Übertragung von Energie in stationäre und bewegte Elektrofahrzeuge - Risch, Florian; Kühl, Alexander; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2011)

Produktionstechnologien für die Antriebe der Zukunft: Anwendungsorientierte Forschung am E|Drive-Center des Lehrstuhls FAPS in Nürnberg - Kühl, Alexander; Mayr, Andreas; Masuch, Michael (Automobiltechnologie in Bayern + e-Car, 2018)

Qualitative assessment of the impact of manufacturing-specific influences on Machine Learning Operations - Raffin, Tim; Reichenstein, Tobias; Klier, Dennis; Kühl, Alexander; Franke, Jörg (Procedia CIRP, 2022)
Machine Learning Operations (MLOps) enables the streamlining of the development and deployment processes of machine learning models; thus, manufacturers can utilize the inherent flexibility and adaptability of Deep Learning at scale to further optimize their processes. This publication provides insights into the challenges that companies face while striving for the efficient operationalization of machine learning algorithms. Moreover, a mapping of capabilities and requirements is presented to provide a baseline for the qualitative analysis of the current state of the art. In conclusion, this article discusses the shortcomings of the existing literature and provides novel implications for MLOps systems in manufacturing.<br

Quo vehis, Electromobility? - Weigelt, Michael; Mayr, Andreas; Böhm, Ralf; Kühl, Alexander; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2018)
The spread of electromobility is still far behind the objectives and expectations of politics and society. Up to now, the relatively high vehicle costs, politically sanctioned energy prices, the limited vehicle ranges and the inconvenient charging process represent the major barriers. At the same time, several drivers exist, such as the superior efficiency, emission-free driving, conservation of fossil resources and the impressive driving enjoyment. This article summarizes the drivers and barriers of the electromobility from an ecological, economic and social perspective. Finally, the challenges for the technology development and the production technology are derive

Quo vehis, Elektromobilität? - Weigelt, Michael; Mayr, Andreas; Böhm, Ralf; Kühl, Alexander; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2018)
Die Verbreitung der Elektromobilität in Deutschland liegt nach wie vor hinter den Zielen und Erwartungen von Politik und Gesellschaft zurück. Bisherige Hemmnisse der Mobilitätswende sind vor allem die relativ hohen Anschaffungskosten von Elektroautos, die politisch sanktionierten Strompreise, die begrenzten Reichweiten sowie der noch wenig komfortable Ladevorgang. Dem stehen wiederum zahlreiche Treiber wie der überlegene Wirkungsgrad, das emissionsfreie Fahren, die Schonung fossiler Ressourcen sowie der beeindruckende Fahrspaß gegenüber. Der vorliegende Beitrag fasst die aktuellen Treiber und Hindernisse der Mobilitätswende aus ökologischer, ökonomischer und sozialer Perspektive zusammen und leitet daraus Herausforderungen an die Technologieentwicklung und Produktionstechnik a

Recycling Concept for Electric Vehicle Drives in the Context of Rare Earth Recovery - Ihne, Thorsten; Hahn, Roman; Wieprecht, Nico; Franke, Jörg; Kühl, Alexander (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
Neodymium Iron Boron (NdFeB) magnets provide the best magnetic properties and are therefore key components for many green technologies. This leads to steeply rising demand for the related rare earth (RE) elements, with e-mobility as central driver. The supply situation for RE magnets is characterized by the dominance of the PR China for the entire value chain causing various problems for the European industry. A potential countermeasure to reduce the dependency on imports is the implementation of a closed raw material cycle within the European Union (EU). Especially the recycling of automotive traction drives provides high potential for the recovery of RE magnets but is complicated by various technical and organizational factors. As result currently no recycling is industrialized for the recovery of RE magnets from traction drives of end-of-life (EOL) electric vehicles (EV).In this context the following paper presents a general concept for the recovery of RE magnets from automotive traction motors. The focus is set on the extraction process of the magnets from the rotor and the related thermal demagnetization step. Finally, the achieved results are evaluated regarding the transferability to a potential series process.<br
Keywords: Electric potential; Europe; Rotors; Electric vehicles; Traction motors; Recycling; Magnets; Rare earth magnets; circular economy; recycling; electromobility; traction drives; thermal demagnetization

Robot-Based Assembly of Cover-Plates - Kühl, Alexander; Franke, Jörg (EMCW Expo, 2014)
Keywords: E|DRIVE; Robot; Stator; Motor; Electric Motor

Robot-based assembly of stators - Kühl, Alexander; Franke, Jörg (2013 3rd International Electric Drives Production Conference, EDPC 2013, 2013)
Keywords: Automated Winding Assembly; Robot-based; Cover; Stator

Robot-Based Assembly of Stators – Methods and Tools to Assembly Windings and Coverplates Robotergestützte Montage von Elektromotorstatoren: Methoden und Werkzeuge zur Montage von Wicklungen und Deckschiebern - Kühl, Alexander; Höft, Annika; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2014)

Robot-based assembly of stator-windings - Kühl, Alexander; Günther, Stefan; Franke, Jörg (Electrical Manufacturing and Coil Winding Expo 2010-2013, 2013)
Keywords: Automated winding assembly; Stator; Robot-based

Robot-based assembly of stator-windings Roboterbasierte Wicklungsmontage: Flexible Statormontage unter Anwendung ambidexterer Kinematiken - Kühl, Alexander; Franke, Jörg (wt Werkstattstechnik - Online, 2013)

Robot-based Forming of Hairpin Winding - Kühl, Alexander; Franke, Jörg (2021 IEEE International Electric Machines and Drives Conference, IEMDC 2021, 2021)
Rotating electrical machines receive an innovative push due to the demands which are made on traction drives. Thus, machines with high power density are required which are produced cost-effectively in large series production. In order to meet these requirements, the use of stators with hairpin winding is a suitable approach, as they have the potential to achieve improved copper filling factors in the stator slots. Furthermore, this technology is also seen as an opportunity to improve the complex and often non-reproducible winding technologies by means of bending, assembly and joining processes. In the design of electric drives, the influences of deviations of the manufacturing processes on the performance are usually not considered. This applies in particular to hairpin winding technology, the manufacture of which requires a large number of bending and contacting operations. These process steps can change the electrical properties of the winding, which changes the behavior of the electrical machine. For this reason, one goal of research at the Institute for Factory Automation and Production Systems (FAPS) is to investigate flexibly automated and reproducible processes for the production of hairpin winding. In the context of the paper, special attention is set on the robot-based forming process and the process-safe conveying of the wire.
CRIS-Team Scopus Importer:2021-08-27
Keywords: bending; electric motor; flexible automation; forming; hairpin; production; robot-based; winding

Robot-based Production of Electric Motors with Hairpin Winding Technolgy - Kühl, Alexander; Riedel, Andreas; Vogel, Alexander; Hartl, Sebastian; Gläßel, Tobias; Franke, Jörg (International Conference on Intelligent Automation and Robotics (ICIAR'19), 2019)

Robotic automatization of handling and contacting the ends of windings for mounting electric drives - Kühl, Alexander; Lebender, Johannes; Franke, Jörg (Lecture Notes in Engineering and Computer Science, 2016)
The connecting process is still one of the most time-consuming processing steps in the production of electric drives. For this reason, the E|Drive-Center at the Institute for Factory Automation and Production Systems (FAPS) from Friedrich-Alexander University Erlangen-Nuremberg (FAU) is researching a solution centered on the flexible automation of this process. This paper examines the possibility of automating the contact of windings' ends in an asynchronous motor with a universal, ambidextrous robot using a contact base. Here, the related ends of the enameled copper wires are connected before plugging in the power supply. In doing so, the robot saves the ends directly after manufacturing the coils in a winding machine and transports them to the face side of the stator. The final connection with the motor periphery is implemented with termination clamps whereby a blade cuts through the wire insulation and produces an electrical connection, while the wiring for the motor concept is actualized by a wiring institution in the form of a plastic ring with printed conducting paths. This form of contacting the ends of windings while mounting an electric drive with a universal, ambidextrous robot has the potential to save time and improve process stability.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Automation; Connecting; robot; Contacting; Electrical drive production; Wiring

Robotic based Assembly of insulating Sleeves onto Winding Coil Ends of Electric Drive Stators - Mahr, Alexander; Mathea, Philipp; Vogel, Alexander; Morello, Andreas; Franke, Jörg; Kühl, Alexander (13th International Electric Drives Production Conference (E|DPC), 2023)
In the production of electrical motors based on the insertion technology, the stator, with a share of 35% of the total costs, is the most expensive component and offers a variety of automation possibilities. In the field of secondary insulation, the application of insulating sleeves onto the stator winding coil ends is usually carried out in manual assembly stations, even in highly automated production lines. This process is a tedious and cost-intensive manual activity. The developments presented in this work show an automated assembly approach for this production step. This invention is based on an industrial robot assembly station that, among other processes, applies commonly used insulation sleeves to the respective winding parts in the stator winding head. With an initial process analysis and the construction of a prototype machine, the basic suitability as an automatable process solution for the assembly of insulation sleeves is presented.<br
Keywords: Insulation; Technological innovation; Windings; Stator windings; Prototypes; Production; Manuals

Robotic-based Automatization of Handling and Contacting of the Ends of Windings for the Mounting of Electric Drives - Kühl, Alexander; Franke, Jörg; Lebender, Johannes (WCECS 2016 - World Congress on Engineering and Computer Science 2016, 2016)
Keywords: E|DRIVE

Schlussbericht zu dem Teilvorhaben "Automatisierte Fertigungstechnologien zum Biegen, Montieren und Schalten von innovativen Formspulenwicklungen" im Verbundprojekt "PRO-E-Traktion" - Gläßel, Tobias; Masuch, Michael; Weigelt, Michael; Kühl, Alexander; Franke, Jörg (2020)
Schlussbericht zu dem Teilvorhaben "Automatisierte Fertigungstechnologien zum Biegen, Montieren und Schalten von innovativen Formspulenwicklungen" im Verbundprojekt "PRO-E-Traktion" ("Automatisierte und robuste Produktionssysteme für E-Traktionsantriebe") Gefördert durch das Bundesministerium für Wirtschaft und Technologie, begleitet durch DLR e. V. Projektträger Förderkennzeichen: 01MX15011F Die Formspulentechnologie gilt als Schlüssel zur Realisierung leistungsdichter elektrischer Traktionsantriebe. Darüber hinaus stellt sie eine Möglichkeit dar, die gegenwärtig schlecht kontrollierbaren Wickelverfahren durch stabilere Biege-, Montage- und Fügeprozesse zu ersetzen. Allerdings waren zum Zeitpunkt des Projektbeginns die benötigten Technologien weder identifiziert, noch entwickelt und qualifiziert. Hier setzt das vorliegende Projekt an, indem es technologische Alternativen für die durchzuführenden Prozessschritte identifiziert und priorisiert. Basierend darauf werden vollautomatisierte Prozessketten zur Herstellung von Statoren mit Hairpinwicklung in unterschiedlichen Stückzahlszenarien konzipiert und in Simulationen validiert. Um darüber hinaus Potentiale alternativer Arten offener Formspulenwicklungen bewerten und gegenüberstellen zu können wird eine Referenzmaschine auf diese übertragen und eine Bewertungssystematik entwickelt und angewandt, in deren Ergebnis die produkt- und fertigungsseitigen Potentiale von Hairpinwicklungen bestätigt werden. Die identifizierten Kernprozesse des Biegens, Montierens sowie der Kontaktierung werden grundlegend analysiert und auf dieser Grundlage die Industrialisierbarkeit der Prozesse abgeleitet. Für die Herstellung der Hairpins zeigt sich eine Kombination des Rotationszugbiegeverfahrens mit einem Gesenkbiegeverfahren als aussichtsreich. Zur Montage der Hairpins in den Stator werden unterschiedliche Konzepte ausgearbeitet und validiert, wobei die Wichtigkeit einer geeigneten Führung der Formspulen herausgearbeitet wurde. Es zeigt sich, dass der Kontaktierung eine wesentliche Rolle in der Prozesskette zukommt, wobei gezeigt wird, dass sich mit einer Kombination aus laserbasierten Isolationsabtrag und Laserstrahlschweißen ein geeigneter Kontaktierungsprozess ableiten lässt. Die erzielten Ergebnisse tragen zu einer Senkung der Hürde bei der vollautomatisierten Herstellung von Statoren mit Formspulen-wicklung bei, da sie die Technologieauswahl, Prozessentwicklung sowie Anlagenplanung maßgeblich vereinfachen Bar-wound windings are regarded to be a key technology to realize electric traction drives with a high power density. Additionally, they provide an opportunity to replace recent winding technologies, that are characterized by a poor controllability, with bending, assembling and joining processes featuring a better process stability. Nevertheless, at the beginning of this project the technologies necessary were neither identified nor developed and qualified. To deal with these issues, the present project identifies and assesses technological alternatives for the process steps necessary. On that basis fully automated production chains for the production of stators with hairpin windings for different production volumes are designed and validated in simulations. Beyond that, the reference winding of this project is conveyed on alternative kinds of bar-wound windings. To be able to compare the resulting concepts, a rating system for bar-wound windings is developed that confirms the potentials of hairpin windings. The key process steps of bending, assembling and contacting identified in this project are analyzed fundamentally and based on these results, industrialization capabilities are derived. For the production of the hairpins, a combination of rotary draw bending and die bending proves to be promising. Different concepts to assemble the hairpins to the lamination are developed and analyzed. It is determined, that a suitable guidance of the bar-wound coil is necessary in any case. The analysis of the contacting process showed, that this process plays an important role in the process chain. Combining a laser based process for the removal of the insulation with a laser welding process is a suitable possibility to realize a reproducible contacting process. The results achieved contribute to a reduction of obstacles for the implementation of a fully automated production of stators with bar-wound windings, as they facilitate the selection of suitable technologies, the development of processes necessary and the planning of production facilities.
Keywords: bar-wound windings; Bending; Biegen; electric mobility; Elektromobilität; Elektromotor; enamelled wire; FKZ: 01MX15011F; Formspulenwicklung; Hairpin; hairpin windings; Hairpinwicklung; INSULATION; Isolation; Lackdraht; Laserschweißen; production technologies; Produktionstechnologien; Pro-E-Traktion; Stator; traction drives; Traktionsantriebe

Simulation supported parameterization of reflow soldering processes Simulationsünterstutzte Parametrierung von Reflowlotprozessen - Kühl, Alexander; Alvarez, Christian; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2011)

Skinning of Insulated Copper Wires within the Production Chain of Hairpin Windings for Electric Traction Drives - Gläßel, Tobias; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (International Journal of Mechanical Engineering and Robotics Research, 2019)
Due to the influence of electric mobility drives used in the automotive powertrain are experiencing a boost in innovation. Caused by the accompanying demand for an increase in power density and the necessity to reduce costs in series production, the winding of electric machines and associated production processes are being improved. A promising novel type of winding is the bar-wound winding, which, in addition to numerous advantages, poses new demands on technologies for their production. In this case the winding is manufactured from a wide range of preformed elements made of enamelled copper wire, which must be connected to each other mechanically and electrically. For this purpose it is necessary to remove the insulation made of thermosetting material from the conducting elements in the joining area. Due to the large number of contacts that have to be prepared in this way, it gets essential to use productive and in particular process-safe skinning technologies. In this paper, the motivation for the application of bar-wound windings and the corresponding production chain is expounded. A method for the metrological quality control of residues in the skinned area is qualified and technologies for the realization of the skinning process are compared. In addition, experiments to create process knowledge for the laser-based removal of the insulation and the skinning by means of rotating brushes are presented.<br
Keywords: electric drives production; electric traction drives; hairpin winding; laser-based skinning; fluorescence based quality assurance

Skinning of insulated copper wires within the production chain of hairpin windings for electric traction drives - Gläßel, Tobias; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (International Journal of Mechanical Engineering and Robotics Research, 2020)
Due to the influence of electric mobility drives used in the automotive powertrain are experiencing a boost in innovation. Caused by the accompanying demand for an increase in power density and the necessity to reduce costs in series production, the winding of electric machines and associated production processes are being improved. A promising novel type of winding with numerous advantages is the bar-wound winding, which introduces new demands on technologies for their production. This winding is manufactured from a wide range of preformed elements made of enameled copper wire, that must be connected to each other mechanically and electrically. For this purpose, it is necessary to remove the insulation of the conducting elements in the joining area. Due to the large number of contacts that have to be prepared in this way, it gets essential to use productive and in particular process-safe skinning technologies. In this paper, the motivation for the application of bar-wound windings and the corresponding production chain is expounded. A method for the metrological quality control of insulation residues in the skinned area is qualified and technologies for the realization of the skinning process are compared. In addition, experiments to create process knowledge for the laser-based removal of the insulation and the skinning by means of rotating brushes are presented.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Electric traction drives; Fluorescence based quality assurance; Hairpin winding; Laser-based skinning

Strategies and Methods for the Energy Efficient Production of Electric Drives - Kreitlein, Sven; Hofmann, Benjamin; Meyer, Alexander Wilhelm; Spreng, Simon; Kühl, Alexander; Franke, Jörg (Procedia CIRP, 2016)
This paper presents methods and experiments for the assessment and evaluation of energy efficiency strategies for manufacturing processes in the field of electric drives production. First, the system for the Least Energy Demand Method will be explained. The basic idea of this calculation is the comparison and evaluation of energy efficiency based on the ratio of the theoretically required energy consumption to the measured energy consumption. Using these values as well as further derived indicators for energy efficiency, the main energy consumers within the field of electric drives production are identified. Subsequently, these processes are analysed and optimized to achieve major energy saving instructions. From an energy point of view during the stator production chain, especially the impregnation process and the joining process have to be optimized as, in the here presented measurements, the impregnation process amounts to more than 80 % of the cumulated energy demands. Moreover, the process of joining insulated copper wires of the stator windings to corresponding cables shoes is optimized, as it shows strong energy saving potentials. Additionally, the power consumption values within the state of the art joining process are varying strongly thus leading to higher load peaks within the production line, which have to be reduced. Regarding energy efficiency within the manufacturing of permanent magnet synchronous rotors, the process of magnet assembly also has to be evaluated. It can be subdivided into magnet manufacturing, logistics, magnetization and assembly. A major part of the energy used in this process is accounted for by means of transportation, especially when considering that magnetized magnets need larger packaging volumes and weights due to the ferromagnetic shielding and spacers to support handling of the magnet bodies. Thus, the energy efficiency can be increased considerably by shifting the magnetization step directly to right before the assembly step. In addition, energy can be saved by optimizing the magnetization process according to the magnetization strategy and the interaction of all process parameters, such as capacity of the magnetizer, inductivity and size of the magnetizing coil, magnet size, material and coating.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Electric drives production; Energy efficiency; Least Energy Demand Method; Manufacturing strategy

StroMiS - Studie zur technisch-wirtschaftlichen Analyse der Stromerzeugung aus Mikrokraftwerken in Serienfertigung - Scholz, Michael; Kühl, Alexander; Höft, Annika; Landgraf, Maximilian; Schneider, Michael; Böhm, Ralf; Badel, Gregor; Lothes, Gerald; Angerer, Kerstin; Hohmann, Andrea; Simon, Peter; Konwitschny, Fabian; et al. (2019)

Systematic Qualification of Layer Thickness, Roundness and Defects of Screen-printed Magnetic Sheets - Schmidt, Alexander; Wieprecht, Nico; Cosack, Alexander; Janisch, Lucas; Franke, Jörg; Kühl, Alexander (2023 13th International Electric Drives Production Conference (EDPC), 2023)
Screen printing offers the potential to produce near net shape and ultra-thin magnetic sheets for electrical machines. This is accompanied by significant potential for increasing performance. In this publication, the influence of various parameters on the geometric green part properties of screen-printed magnetic sheets is systematically analyzed by statistical design of experiment. The factors iron paste, design, substrate carrier and squeegee speed on the quality characteristics layer thickness, roundness, defects, and cycle time are considered. The aim of the investigation is to determine the main influencing factors and interactions on the target variables and the subsequent derivation of suitable parameter combinations by target variable optimization.<br
Keywords: Printing; Electric potential; Systematics; Shape; Production; Magnetic analysis; Substrates; Additive Manufacturing; Electric Motor; Magnetic Sheets; New Materials; Screen Printing

Technical, Economical and Ecological Potentials of Electrified Roads - Franke, Jörg; Weigelt, Michael; Kneidl, Maximilian; Masuch, Michael; Kühl, Alexander (Wiener Produktionstechnik Kongress 2022, 2022)

Techno-Economic Evaluation of Technological Alternatives to Extend the Range of Electric Vehicles - Weigelt, Michael; Mayr, Andreas; Kühl, Alexander; Batz, Kilian; Bican, Peter; Russer, Johannes A.; Russer, Peter; Franke, Jörg (5th Annual Conference on Electric Roads & Vehicles, 2018)

Technologies and processes for the flexible robotic assembly of electric motor stators - Kühl, Alexander; Furlan, Stefan; Gutmann, Joschka; Meyer, Manuel; Franke, Jörg (2017 IEEE International Electric Machines and Drives Conference (IEMDC), 2017)

Thermal Analysis of the Encapsulation of Resonance Circuit Modules for the Paving Into Electric Road Systems - Kneidl, Maximilian; Kneidl, Maximilian; Gömmel, Daniel; Jordan, Sophia; Masuch, Michael; Kühl, Alexander; Franke, Jörg (Proceedings of 2024 IEEE Wireless Power Technology Conference and Expo, WPTCE 2024, 2024)
Electric Road Systems (ERS) for electric vehicles seem to be a promising solution to increase the range of electric vehicles without having to use larger batteries. Therefore, the resonance circuits have to be deployed into the roadways very precise to ensure best transmission efficiency and no breakdowns due to insufficient installation. Beside the manufacturing and deployment processes, the product properties have to be adapted to the requirements of road construction technologies. The main objective of this paper is to use simulation results and practical validation of materials and systems to determine the thermal requirements of resonant coil circuits for ERS. From the construction technologies of asphalt roads as well as the operation of electric road systems, the resulting material requirements for the encapsulation are determined. By characterization of different insulation materials, simulation models on the thermal impact of the system components are derived. The models are validated through practical test setups. The results provide knowledge that can be used to optimize the product design to different use cases in operation as well as construction.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Manufacturing; Simulation; Thermal Optimization; Wireless Power Transfer

Thermische Simulation von Werkzeugmaschinen zur Verbesserung der Fertigungsgenauigkeiten: Thermal simulation of machine tools for the advancement of the production accuracy - Kühl, Alexander; Franke, Jörg (Integrationsaspekte der Simulation, 2010)
Keywords: E|DRIVE; E|P

Vision-Based Pose Estimation of Superimposed Enameled Wire Ends for Robotic Handling of Powerdense Flat Wire Stators - Henrich, Valentin; Vogel, Alexander; Baader, Marcel; Franke, Jörg; Kühl, Alexander (2024 14th International Electric Drives Production Conference (EDPC), 2024)
In the production of electric drives, achieving highly efficient performance in new use cases is essential to meet global climate targets. To maximize motor power while minimizing motor weight, the stator slots must be filled with as much copper as possible. Traditionally, round wires have been the standard; however, with increasing efficiency demands, they can no longer meet performance expectations. Form coils, also known as hairpins, offer a higher fill factor and are becoming a more common technology. In addition, continuous winding processes using flat or rectangular wires are under development, which could meet future demands for electric drives. Along with new joining solutions, this technology has the potential to reduce production costs while minimizing contact points that could otherwise increase contact resistance. A key aspect of automating these processes is the precise and reliable detection of wire positions, which is critical for achieving a fully automated process chain. In this paper, an AI-based algorithm for flat wire detection is proposed, enableling seamless integration in robot-based systems, ensuring accurate wire positioning throughout the production stages. By incorporating AI-driven recognition methods, high-quality and efficient automation of electric drive manufacturing processes can be realized, from the initial winding steps to final end-of-line testin
Keywords: wire detection; flat wire; image recognition; 3D wire reconstruction; densely packed object recognition; electric drives production